2016
DOI: 10.12669/pjms.325.10457
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural abnormalities of the kidney and urinary tract in severely malnourished children - A hospital based study

Abstract: Objectives:The association of malnutrition and systemic diseases like chronic kidney disease (CKD) is well known. Various urinary tract abnormalities may be associated with malnutrition. So objective of current study was to determine the frequency of functional and structural urinary tract abnormalities in severely malnourished children admitted in Nutritional Rehabilitation Unit (NRU) of a tertiary care facility, Karachi.Methods:This descriptive cases series of 78 children was conducted in NRU from October 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…A total of 16 patients with 17 kidneys were determined to have pathological fetal HY, accounting for 9.9% of all HY patients, and the HY in the remaining cases regressed after birth. Previous studies revealed that pathological HY is mainly caused by structural abnormalities of the renal pelvis system and urine reflux (6,19). The present study indicated that 9 patients, accounting for 56.3% of all pathological HY cases, had stenosis at the ureteropelvic junction, which was the leading cause of pathological HY in this cohort.…”
Section: Discussionsupporting
confidence: 55%
“…A total of 16 patients with 17 kidneys were determined to have pathological fetal HY, accounting for 9.9% of all HY patients, and the HY in the remaining cases regressed after birth. Previous studies revealed that pathological HY is mainly caused by structural abnormalities of the renal pelvis system and urine reflux (6,19). The present study indicated that 9 patients, accounting for 56.3% of all pathological HY cases, had stenosis at the ureteropelvic junction, which was the leading cause of pathological HY in this cohort.…”
Section: Discussionsupporting
confidence: 55%
“…Most of the studies were from African countries including South Africa [1315, 34–36] Nigeria [11, 3740], Uganda [41, 42], Kenya [17, 43] Tanzania [18, 44], Ethiopia [16] Niger [12], Sudan [45], and Gambia [19]. Other studies were conducted in Turkey [46, 47], India [4, 48, 49], Pakistan [50, 51], Bangladesh [52], Thailand [53], Iran [54], Australia [55], Peru [56], and Jamaica [57]. Sample size varied, with 18% of the studies having < 50 participants.…”
Section: Resultsmentioning
confidence: 99%
“…Complicated malnutrition if accompanied by anorexia and/or Kwashiorkor with bilateral pitting edema and/or another severe condition.Severe malnutrition with 15.4% being edematousFoley catheterDipstick urinalysis, Culture using CHRO Magar inoculation plate and sensitivity using Kirby Bayer disk diffusion method on Mueller-Hinton agar.Single pathogen ≥10 4 /ml ( Escherichia coli ) or ≥ 10 5 /ml (others) regardless of the number of leukocytes in urine OR bacteriuria ≥10 3 /ml ( Escherichia coli ) or 10 4 /ml (others in the presence of at least 10 4 leukocytes/ml in the urineSameen I and Moorani N 2014 [50]Weight for height Z scores (below -3 SD with or without bilateral pitting edema and any of the following: anorexia, severe anemia, high fever, severe dehydration, and systemic infection.Severe malnutrition including severe wasting (80.8%) and edematous malnutrition (19.2%)Not specifiedUrine culture and sensitivityNot specifiedAhmed M et al 2015 [18]Weight-for-height < 3 SD of the z score according to WHO Classification (Mild (−1 SD) or moderate (−2 SD) or severe (−3SD)All. Mild (36.6%), moderate (19.2%) and severe (44.3%)Mid-stream urine (if > 24 months) or suprapubic aspiration (if < 24 months)Culture (cysteine lactose electrolyte deficient agar (CLED), MacConkey and blood agar plates (Oxoid UK) incubated at 37 degrees for 24 h. Drug susceptibility using disc diffusion methodAny growth from suprapubic aspiration or ≥ 10 5 /ml of mid-stream urineAnjum M et al 2016 [51]Presence of bilateral pitting edema or weight for height z score > − 3 of the NCHS/WHO reference valuesSevere malnutrition including marasmus (82%) and edematous malnutrition (18%)Not specifiedMicroscopy and cultureNot specifiedThuo N et al 2017Pedal edema (kwashiorkor or marasmic kwashiorkor) or weight for height Z score ≤ − 3 or mid-arm circumference < 11 cm (if length > 65 cm)Severe (36% with edema)Mid-stream urineMicroscopy, culture in cystine lactose electrolyte deficient agar at 37 degrees and sensitivityGrowth of a single pathogen at ≥50 colony forming units/μlCase-control studiesBuchanan N et al 1971 [34]Atrophic malnutrition or kwashiorkorModerate/severe malnutrition including kwashiorkor: (33.3%) and atrophic malnutrition: (66.7%)midstream urine or sterile urine bags or suprapubic aspirationUricult dip-slide (nutrient agar on one side and McConkey’s agar on the other side, each medium covering 13 cm 2 slide area) incubated at 37 °C for 16–24 h. Confirmation using conventional pour plate method for suprapubic urine specimen> 10 5 organisms/ml of urineFreyre EA et al 1973 [56]Marasmus, Marasmic Kwashiorkor or KwashiorkorSevere malnutrition including marasmus (39%), kwashiorkor (20%) and marasmic kwashiorkor (41%).Sterile plastic urine collectorCulture using the Henrich method…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings have been published recently by us. 12 Significant proportion of children (79.48%) were ≤ 2 years so this may also be explained on the maturity of kidney function as we know that GFR become equal to adult level by the age of 18-24 months. 7…”
Section: Discussionmentioning
confidence: 99%